(untitled) - ANDRIANI, ROSI (Jurnal Pendidikan Tata Niaga (JPTN), 2013)
One of the new industrial competition drink or food ready to compete and enter the market nationally is coffee white industry. However, competition in the coffee industry white or white coffe has become more rigorous in the range of a short time. Therefore, as producer pioneer pt. A java prima perennial should be able to innovate with marketing strategies effective and well-planned in order to increase the decision of the purchase of products kopi luwak white koffie. Research is aimed to know the influence of the quality of products and attractiveness advertising simultaneously and partial of the decision of a purchase. The population of this research is a student economics faculty ever buy and consume kopi civet white koffie and samples to be taken as much as 110 respondents and use sampling techniques and purposive aksidental sampling. Research with the use of the test results show that the quality of the product f attraction and advertising influential simultaneously with the resolution of the purchase Keywords: the quality of the product attractiveness advertising, the decision of the purchase